Các nhóm danh lượng từ tiếng Hán và nghĩa của chúng =Groups of Chinese nominal classifiers and their meaning /Nguyễn Hồng Nam. - Nguyễn, Hồng Nam
The term “ classifier” or “ measure word” is a part of speech, which is classified and named after examining 11 Chinese basic word classes. The study into various types of meanings of nomial classifiers has an important role in the research of Chinese grammar. It characterizes a particular feature of Chinese grammar and is a very useful tool for building the general grammartical system of this language. This article aims to collect, classify and analyze the meaning geature of each type of Chinese nominal classifiers.